2016
DOI: 10.1111/1346-8138.13219
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary palmoplantar keratoderma “clinical and genetic differential diagnosis”

Abstract: Hereditary palmoplantar keratoderma (PPK) is a heterogeneous group of disorders characterized by hyperkeratosis of the palm and the sole skin. Hereditary PPK are divided into four groups -diffuse, focal, striate and punctate PPK -according to the clinical patterns of the hyperkeratotic lesions. Each group includes simple PPK, without associated features, and PPK with associated features, such as involvement of nails, teeth and other organs. PPK have been classified by a clinically based descriptive system. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 57 publications
1
50
2
Order By: Relevance
“…It is characterized by hyaline deposits in skin and mucous membranes of the upper aerodigestive tract and intracranial calcifications may be present. 1,2 Our patient displayed typical symptoms like hoarseness since birth, waxy yellow papules on the eyelid margins, hands, penis and scrotum as well as a thickened, papillomatous tongue and buccal mucosa. Furthermore, tongue protrusion was restricted ( Fig.…”
Section: Dear Editorsmentioning
confidence: 75%
See 1 more Smart Citation
“…It is characterized by hyaline deposits in skin and mucous membranes of the upper aerodigestive tract and intracranial calcifications may be present. 1,2 Our patient displayed typical symptoms like hoarseness since birth, waxy yellow papules on the eyelid margins, hands, penis and scrotum as well as a thickened, papillomatous tongue and buccal mucosa. Furthermore, tongue protrusion was restricted ( Fig.…”
Section: Dear Editorsmentioning
confidence: 75%
“…Palmoplantar keratoderma: creating a disease burden questionnaire Dear Editor, Palmoplantar keratoderma (PPK) constitutes a heterogenous group of disorders that may be further subdivided into hereditary and acquired forms, characterized by hyperkeratosis of the palm and sole skin. 1,2 In recent years, the exponentially increasing use of next-generation sequencing technologies has led to the identification of several novel disease genes, substantially contributing to better comprehend PPK's molecular basis. PPK involvement may severely limit normal activities and lead to palmar retractions, digital amputations due to ischaemic strictures and intense pain requiring major analgesic therapy.…”
mentioning
confidence: 99%
“…Based on the distribution pattern of hyperkeratotic lesions, PPKs are clinically classified into four types: diffuse, striate, focal and punctate. 1,2 To date, more than 20 genes have been reported to be responsible for PPKs. 1,2 Although the majority of reported heterozygous loss-of-function mutations in the gene encoding desmoglein 1 (DSG1), a key molecule for epidermal adhesion and differentiation, are associated with striate PPK, 3 a very limited number of studies have suggested that dominant DSG1 mutations also cause non-striate PPK.…”
Section: Loss-of-function Mutation In Dsg1 Underlies Focal Palmoplantmentioning
confidence: 99%
“…Palmoplantar keratodermas (PPKs) are rare skin disorders characterized by profound thickening of the skin, particularly on the palms of the hands and the soles of the feet, as a result of hyperkeratosis. PPKs can be acquired through malnutrition, inflammatory disease, paraneoplastic effects or chemical exposure, but are most commonly inherited . Gain‐ or loss‐of‐function mutations in at least 25 genes have been implicated in hereditary PPK, although the total may be substantially higher (https://panelapp.genomicsengland.co.uk/WebServices/list_panels/).…”
mentioning
confidence: 99%